2020
DOI: 10.1007/s12144-020-00946-3
|View full text |Cite
|
Sign up to set email alerts
|

Depression and sleep quality among Chinese college students: The roles of rumination and self-compassion

Abstract: A large number of studies have examined the association between depressive symptoms and sleep quality, however, the psychological mechanism underlying the association remains nebulous. Using moderated mediation analysis, the present study aimed to examine to what extent the association was mediated by rumination and whether the mediation effect was moderated by self-compassion. Self-reported measures on depressive symptoms, rumination, self-compassion, and sleep quality were collected from 564 college students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
6
3
Order By: Relevance
“…The present study showed that the global PSQI score was no signi cantly correlated with age, which was inconsistent with the previous ndings (Bian et al, 2020). These discrepancies maybe explained that the mean age was comparably low and the age range was restricted in our sample.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study showed that the global PSQI score was no signi cantly correlated with age, which was inconsistent with the previous ndings (Bian et al, 2020). These discrepancies maybe explained that the mean age was comparably low and the age range was restricted in our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of sex disparities in sleep quality, our results were inconsistent with several previous studies (Bian et al, 2020;Neumann et al, 2020;Sa et al, 2020). For example, Bian et al (2020) found that females had a higher PSQI score than males. Sa et al (2020) found that females had lower days of getting enough sleep in a week.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding that rumination functions as one mediating mechanism linking stress to poor sleep quality was consistent with previous studies [ 13 , 25 , 53 ]. This further evidences that ruminative behavior and thinking can emerge in the presence of uncontrollable factors such as unprecedented and repetitive COVID-19 stressors [ 17 ] and that perseverative cognition can be health-threatening due to its function to sleep quality [ 22 ].…”
Section: Discussionmentioning
confidence: 92%
“…Further, rumination was found to have associations with short- and long-term sleep disturbances among college students [ 22 , 23 ] partly due to the continuous psycho-physiological arousals in response to stressful life events [ 20 ]. Although studies conducted pre-COVID-19 [ 24 ] have found little evidence of the effect of rumination on sleep among individuals with little rumination disposition, recent studies have proposed that the sudden and pervasive nature of COVID-19 may develop rumination tendencies among those have previously not shown such issues [ 13 ].…”
Section: Introductionmentioning
confidence: 99%